PENERAPAN PELAPORAN PAJAK BERBASIS E-FILING DALAM UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK - Agus Salim HR; Faidul Adzim; Reza Wahyudi (Jurnal Riset Perpajakan: Amnesty, 2020)
The study aims to find out how the influance of E-filing in effort to increase the obligation of taxpayers in the southerm makassar tax service office. The subject of the study is the southerm makassar tax service office. This research data collection technique is by conduction observation and interviews directly with parties. This result of this study apply that the exixtence of an E-filing based tax reporting system can improve tax complience is very effective. This can be seen from secondary data obtained from the parties concerned.